Expression of Talin-1 in endometriosis and its possible role in pathogenesis - Xian Tang; Qing Li; Lijie Li; Jianfa Jiang (BMC, 2021)
Abstract Background Endometriosis is a disease that involves active cell invasion and migration. Talin-1 can promote cell invasion, migration and adhension in various cancer cells, but its role in endometriosis has not been investigated. This study was to investigate the expression level of Talin-1 in endometriosis and the role of Talin-1 in the proliferation, adhesion, migration, and invasion of human endometrial stromal cells (ESCs). Methods Ectopic and eutopic endometrial tissues were collected from women with endometriosis, and the control endometrial tissues were obtained from patients without endometriosis. The expression level of Talin-1 was detected in each sample using quantitative real-time polymerase chain reaction and immunohistochemistry. The expression of Talin-1 was inhibited using RNA interference in ESCs, and its proliferation, apoptosis, adhesion, migration, and invasion capacity were analyzed. Western blotting was performed to detect the expression of related molecules after the downregulation of Talin-1. Results The results showed that the mRNA and protein expression of Talin-1 were significantly increased in the ectopic endometrium and eutopic endometrial tissues compared with the controls. The knockdown of Talin-1 did not affect the proliferation and apoptosis of ESCs. The results indicated that the downexpression of Talin-1 inhibited the adhesion, invasion, and migration of ESCs. In addition, the expressions of N-cadherin, MMP-2, and integrin β3 were significantly lower after the deregulation of Talin-1, whereas the levels of E-cadherin were significantly increased. Conclusions The expression of Talin-1 was increased in the ectopic and eutopic endometrial tissues compared with the control endometrium. The downregulation of Talin-1 inhibited the adhesion, invasion, and migration of ESCs.